1998
DOI: 10.1152/ajpgi.1998.274.6.g1077
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic trypsinogen I expression during cell growth and differentiation of two human colon carcinoma cells

Abstract: Pancreatic trypsin has been found to induce tight junction or dome formation in some colon cancer cell lines (HT-29, Caco-2), and a tumor-associated trypsinogen, trypsinogen type II, has been isolated from another colon cancer cell line (COLO 205). We have tried to determine if trypsinogen is present and how its expression varies during cell culture in HT-29 Glc+/− and Caco-2 cells, which exhibit enterocytic differentiation, and in HT-29 Glc+ cells, which never differentiate. Trypsinogen mRNA presence and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…In this context, it is worth pointing out that several lines of evidence indicate the importance of locally secreted trypsin at the vicinity of colon tumours: (1) trypsin was shown to be expressed by the large intestine . Normal epithelial cells surrounding colon tumour cells are a likely source of active trypsin; (2) human colon cancer cells themselves were shown to express trypsin and trypsinogen (Bernard-Perrone et al, 1998;Miyata et al, 1999); (3) recent studies on gastric cancer indicate that blood vessels surrounding tumours express trypsin, whereas other blood vessels do not . Trypsin is also present in serum at nanomolar concentrations and could diffuse from blood to tumour cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is worth pointing out that several lines of evidence indicate the importance of locally secreted trypsin at the vicinity of colon tumours: (1) trypsin was shown to be expressed by the large intestine . Normal epithelial cells surrounding colon tumour cells are a likely source of active trypsin; (2) human colon cancer cells themselves were shown to express trypsin and trypsinogen (Bernard-Perrone et al, 1998;Miyata et al, 1999); (3) recent studies on gastric cancer indicate that blood vessels surrounding tumours express trypsin, whereas other blood vessels do not . Trypsin is also present in serum at nanomolar concentrations and could diffuse from blood to tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Extra-pancreatic production of trypsin was shown in ovarian (Hirahara et al, 1995), lung (Kawano et al, 1997), gastric and colonic tumours (Bernard-Perrone et al, 1998;Miyata et al, 1999); 2. The trypsinogen gene is significantly expressed in vascular endothelial cells around gastric tumours ; 3.…”
mentioning
confidence: 99%
“…Therefore, EP localization on the luminal surface of the duodenal villi may contribute to enterocyte growth by generating active trypsin on the cell surface. Recently, it was reported that trypsinogen is expressed by various human epithelial cells (18) and is also secreted by human tumor cells including gastric (13) and colon cancer cells (2). Trypsinogen production was associated with metastatic phenotypes of these human cancer cells (13,25).…”
Section: Discussionmentioning
confidence: 99%
“…Extra-pancreatic production of trypsin was shown in ovarian (5), lung (6), gastric (7), and colonic tumors (8) and also in colon cancer cell lines (9,10). In addition, overexpression of exogenous trypsinogen cDNA in human gastric cancer cells increases their tumorigenicity in nude mice (7).…”
mentioning
confidence: 99%